Cellulose Surface Degradation by a Lytic Polysaccharide Monooxygenase and Its Effect on Cellulase Hydrolytic Efficiency - Eibinger, Manuel; Ganner, Thomas; Bubner, Patricia; Rošker, Stephanie; Kracher, Daniel; Haltrich, Dietmar; Ludwig, Roland; Plank, Harald; Nidetzky, Bernd (The Journal of biological chemistry, 2014)
Lytic polysaccharide monooxygenase (LPMO) represents a unique principle of oxidative degradation of recalcitrant insoluble polysaccharides. Used in combination with hydrolytic enzymes, LPMO appears to constitute a significant factor of the efficiency of enzymatic biomass depolymerization. LPMO activity on different cellulose substrates has been shown from the slow release of oxidized oligosaccharides into solution, but an immediate and direct demonstration of the enzyme action on the cellulose surface is lacking. Specificity of LPMO for degrading ordered crystalline and unordered amorphous cellulose material of the substrate surface is also unknown. We show by fluorescence dye adsorption analyzed with confocal laser scanning microscopy that a LPMO (from Neurospora crassa) introduces carboxyl groups primarily in surface-exposed crystalline areas of the cellulosic substrate. Using time-resolved in situ atomic force microscopy we further demonstrate that cellulose nano-fibrils exposed on the surface are degraded into shorter and thinner insoluble fragments. Also using atomic force microscopy, we show that prior action of LPMO enables cellulases to attack otherwise highly resistant crystalline substrate areas and that it promotes an overall faster and more complete surface degradation. Overall, this study reveals key characteristics of LPMO action on the cellulose surface and suggests the effects of substrate morphology on the synergy between LPMO and hydrolytic enzymes in cellulose depolymerization. Lytic polysaccharide monooxygenase (LPMO) has recently been discovered to depolymerize cellulose. Dynamic imaging was applied to reveal the effects of LPMO and cellulase activity on solid cellulose surface. Critical features of surface morphology for LPMO synergy with cellulases are recognized. Direct insights into cellulose deconstruction by LPMO alone and in synergy with cellulases are obtained.